Bioresorbable silicon electronic sensors for the brain - Kang, Seung-Kyun; Murphy, Rory K. J.; Hwang, Suk-Won; Lee, Seung Min; Harburg, Daniel V.; Krueger, Neil A.; Shin, Jiho; Gamble, Paul; Cheng, Huanyu; Yu, Sooyoun; Liu, Zhuangjian; McCall, Jordan G.; et al. (Nature (London), 2016)
Electronic implants are often used in diagnosing and treating human illness, but permanent implants come with problems; here, devices are described that can sense temperature, pressure, pH or thermal characteristics, and—crucially—are fully resorbable by the body. A bioresorbable electronic interface to the brain This study reports the design, fabrication, and in vivo implementation of a silicon-based bioresorbable sensor for monitoring the pressure and temperature within the brain. Individually, all the materials that form the device were previously known to be resorbable. But this is the first demonstration of a functional sensor that completely dissolves in vivo after use with no apparent ill effects. Making the sensors completely resorbable avoids the need for surgical removal. The applications of such devices are not restricted to the brain — they can be modified for use in a range of medical conditions. Percutaneous wires were eliminated by implanting a telemetry device, though this device was not completely resorbable. Many procedures in modern clinical medicine rely on the use of electronic implants in treating conditions that range from acute coronary events to traumatic injury 1 , 2 . However, standard permanent electronic hardware acts as a nidus for infection: bacteria form biofilms along percutaneous wires, or seed haematogenously, with the potential to migrate within the body and to provoke immune-mediated pathological tissue reactions 3 , 4 . The associated surgical retrieval procedures, meanwhile, subject patients to the distress associated with re-operation and expose them to additional complications 5 , 6 , 7 , 8 . Here, we report materials, device architectures, integration strategies, and in vivo demonstrations in rats of implantable, multifunctional silicon sensors for the brain, for which all of the constituent materials naturally resorb via hydrolysis and/or metabolic action 9 , 10 , 11 , 12 , eliminating the need for extraction. Continuous monitoring of intracranial pressure and temperature illustrates functionality essential to the treatment of traumatic brain injury 2 , 13 ; the measurement performance of our resorbable devices compares favourably with that of non-resorbable clinical standards. In our experiments, insulated percutaneous wires connect to an externally mounted, miniaturized wireless potentiostat for data transmission. In a separate set-up, we connect a sensor to an implanted (but only partially resorbable) data-communication system, proving the principle that there is no need for any percutaneous wiring. The devices can be adapted to sense fluid flow, motion, pH or thermal characteristics, in formats that are compatible with the body’s abdomen and extremities, as well as the deep brain, suggesting that the sensors might meet many needs in clinical medicine.